Analysis of a Qur'anic topic in Islamic education textbook: human creation as a sign of Allah's greatness - Ismail, Halim; Hassan, Hilmiah; Khalid, Madihah; Sahrir, Muhammad Sabri (University of Malaya, 2022)
This study aims to analyze and evaluate a Quranic-based topic from a chapter of the Islamic Education for secondary school textbook authorized by the Ministry of Education, Malaysia. Textbooks are an essential feature in Malaysian classrooms when implementing the school curriculum. Due to the development and changes in practices and teaching methodology, the quality must be considered before the choice of a specific textbook is made. Policymakers, teachers, and educators should inspect the textbook's content accuracy and recommended teaching and learning practices before determining its suitability. This will benefit teachers and students, leading to meeting the educational objectives. This qualitative study used a content analysis approach to examine the pedagogical value and suitability of a topic and its content with respect to students’ cognitive, affective and psychomotor learning domains. After analyzing the data, it was shown that the examined topic met students’ capability to interpret the lesson well. A solution to overcome shortcomings was also suggested. The findings from this study will be beneficial to teachers in adapting the recent technique of teaching. It will also benefit the policymakers in making amendments to the subjects’ Curriculum and Assessment Standard Document (DSKP).